Synthesis of TPGS/Curcumin Nanoparticles by Thin-Film Hydration and Evaluation of Their Anti-Colon Cancer Efficacy In Vitro and In Vivo - Li, Hong; Yan, Liping; Tang, Edith K.Y.; Zhang, Zhen; Chen, Wei; Liu, Guohao; Mo, Jingxin (Frontiers in Pharmacology, 2019)
Curcumin (CCM) has many potential uses in anticancer chemotherapy, but its low water solubility poses a major problem preventing translation into the clinic. TPGS is a water-soluble derivative of vitamin E that acts as a surfactant with the ability to form micellar nanoparticles in water. More importantly, TPGS acts as a potent antioxidant that can neutralise intracellular reactive oxygen species (ROS). In this study, we solubilised CCM with TPGS using thin-film rehydration to prepare aqueous formulations containing CCM at clinically relevant concentrations. We found that the minimal TPGS:CCM ratio for producing nanoparticles was 5:1 (w/w): at or above this ratio, stable nanoparticles formed with an average particle diameter of 12 nm. CCM was released from TPGS/CCM micelles in simulated colonic and gastric fluids. TPGS/CCM nanoparticles decreased intracellular ROS levels and apoptosis as well as inhibited migration of HT-29 human colon cancer cells more potently than free CCM. Pharmacokinetic analysis showed TPGS/CCM to be more bioavailable than free CCM after oral administration to rats. Our results suggest that TPGS/CCM may increase therapeutic efficacy of CCM against colon cancer and merits further investigation in a clinical setting.